Analyzing dprE1 gene variations in drug-resistant Mycobacterium tuberculosis isolates from Northern Thailand - Phyo, Zayar; Wattananandkul, Usanee; Intorasoot, Sorasak; Saikaew, Sukanya; Yimcharoen, Manita; Butr-Indr, Bordin (Journal of Associated Medical Sciences, 2024)
Background: DprE1 has been discovered as a highly promising candidate for eradicating multidrug-resistant tuberculosis (MDR-TB) due to its localization and crucial role in cell wall synthesis. Several DprE1 inhibitors in clinical trials target different binding sites on the DprE1 protein. However, mutations in these binding sites can result in resistance to these inhibitors. Nonetheless, only a few reports exist on the sequence analysis of the dprE1 gene in drug-resistant clinical isolates, especially in Thailand, a country with a high TB burden. Objective: To investigate the genetic variations in the dprE1 gene among drugresistant clinical Mycobacterium tuberculosis (Mtb) isolates from Northern Thailand and to examine mutations known to confer resistance to specific inhibitors. Materials and methods: Drug resistance profiles of 19 clinical Mtb isolates from Northern Thailand—11 multidrug-resistant Mtb, 2 isoniazid-resistant Mtb, and 6 rifampicin-resistant Mtb-were assessed using the agar proportion method and Sanger sequencing. New PCR and sequencing primers were designed to cover the entire length of the dprE1 gene. Mutation profiles were detected by performing DNA alignment against the reference strain, M. tuberculosis H37Rv, using BioEdit Sequence Alignment version 7.2.5. The distribution of these mutations was assessed through the Basic Local Alignment Search Tool (BLAST) server. Visual representation of amino acid mutation regions in DprE1 was generated using the PyMOL 3.0. Results: The mutation at codon 387 associated with benzothiazinone (BTZ) compounds was not observed in the dprE1 gene of any clinical isolates. The most common mutation profile, C→T at codon 459, was found in 73.68% of clinical isolates. However, this is a silent mutation and probably indicates genetic polymorphism. Non-synonymous substitutions in the dprE1 gene were detected: A356T in one INH-R isolate and V400I in two RIF-R isolates. BLAST analysis revealed that the A356T mutation in the INH-R isolates had a 100% match with sixteen Mtb strains from other regions. Interestingly, the V400I mutation in the RIF-R isolates had not been reported, making this the first documentation of such a finding. Conclusion: Although no mutations directly linked to resistance against current DprE1 inhibitors were found, mutations in the DprE1 binding sites could affect the efficacy of these inhibitors. This study highlights the significance of mono-drugresistant strains that acquire dprE1 mutations, potentially complicating future TB treatment targeting DprE1.